Accelerated transfer and separation of charge carriers during the photocatalytic production of hydrogen over Au/ZrO2–TiO2 structures by interfacial energy states. (15th May 2023) - Ramírez-Ortega, David; Guerrero-Araque, Diana; Sierra-Uribe, Jhon Harrison; Camposeco, Roberto; Gómez, Ricardo; Zanella, Rodolfo
Abstract: Energy states and surface plasmon resonance (SPR) play an important role in photocatalytic processes and power generation energy, for they improve the separation, transport, and mobility of charge carriers. The creation of Au/semiconductor heterostructures with different amounts of Au forms energy states that can modulate surface plasmon excitation, interfacial charge transport and photocatalytic activity to generate hydrogen. However, the Au loading effect on the interfacial charge transport and photocatalysis of plasmonic Au/semiconductors is unclear. For this reason, in this study, Au/ZrO2 –TiO2 materials with different Au loadings were synthesized and evaluated in the photocatalytic production of hydrogen. The results confirmed boosted photoactivity with increased gold loading up to 5 wt.%, obtaining four times more hydrogen production than with the base material. The (photo) electrochemical measurements revealed that the Au inclusion provoked the adjustment of Fermi level values associated with the variation of surface energy states at the Au/ZrO2 –TiO2 interface, which can be related to the modulation of SPR. This phenomenon can be explained by two simultaneous effects: i) the creation of energy states at the Au/ZrO2 –TiO2 interface that modify the Fermi level to more negative potentials with respect to the base material, in order to have photogenerated electrons with higher reducing power to catalyze the hydrogen production; and ii) the Au metallic nanoparticles with SPR act as electronic reservoirs that extend the life time of photogenerated electron-hole pairs, thus enhancing the separation of charge carriers and the mobility of photogenerated electrons. Graphical abstract: Image 1 Highlights: Nanometric Au formed onto ZrO2 –TiO2 by the deposition-precipitation with urea. XPS evidenced the contribution of Au species and the interaction between ZrO2 and TiO2 . (Photo)electrochemical measurements evidenced the formation of energy states at the interface. Hydrogen production increased 4 times by using Au nanometric metallic co-catalyst. Au metallic nanoparticles acted as "electronic reservoirs".